Case study on the diving ability of the Bajo tribe in Indonesia - Sandra Arhesa; Amung Ma'mun; Boyke Mulyana; Nina Sutresna; Silvia Agustin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The Bajo community possesses remarkable abilities and has been the focus of various studies. However, a comprehensive understanding of the complex factors influencing their diving capabilities remains incomplete.